Soil as a process: Anthropo-pedogenesis and regenerative design in post-mining landscapes - Simoni, Davide (Journal of Delta Urbanism, 2026)
This article reframes the role of soil in urbanism through the lens of anthropo-pedogenesis—the process by which human activity interacts with, alters, and co-produces soil. Rather than treating soil as a static support or a neutral background, the study positions it as a living, evolving medium shaped by complex interplays between ecological processes and socio-technical systems. Within this framework, soil becomes both an archive of past transformations and a substrate for future territorial projects. The empirical focus is the Sulcis-Iglesiente region in south-western Sardinia, a former mining district marked by extensive soil disturbance, infrastructural remnants, and post-industrial fragilities. By analyzing its stratified deposits, infrastructural logics, and patterns of contamination and regeneration, the study reveals the emergence of a new “technical thickness”—a hybrid terrain where natural and artificial layers overlap. From this condition, the article proposes a project of anthropo-pedogenesis: a soil-oriented design approach that embraces long temporalities, partial recoveries, and adaptive transformations. It argues for a shift from remediation to coexistence, from erasure to care, calling on urbanism to engage with disturbed soils not as waste, but as living, negotiable materials. In doing so, it offers a framework for regenerative design rooted in the metabolic reconfiguration of post-extractive landscapes.